Прогноз типов разреза Баженовской свиты с помощью классификации; EAGE/SPE Joint Workshop on Shale Oil 2015 - Буханов Н. В. Никита Владимирович; Белозёров В. Б. Владимир Борисович; Демьянов В. В. Василий Валериевич; Евдокимов А. В. Антон Валерьевич (2015, 2015)
Title screen